A study on the possible renovation of a 1960's house - Lopez, Ma. Blesilda R.; Mayo, Adelaida Villaraza (1998.)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BID)--University of the Philippines Diliman.
Keywords: Dwellings -- Remodeling -- Philippines